Differences in Academic Dishonesty Viewed from Gender and School Majors - Sahin, Arif; Sugiyo, Sugiyo; Sunawan, Sunawan (Universitas Negeri Semarang, 2022)
A common thing done by students to get a good score is to cheat. This study aimed at examining the differences in academic dishonesty viewed from gender and majors in vocational high school (SMK) students throughout Godong Sub-district in Grobogan Regency. It involved 286 students. Their data were analyzed using a two-way anova test. Findings showed that (1) there found a difference in the academic dishonesty viewed from majors in which the electric power installation engineering department had the lowest academic dishonesty rate and the computer network engineering major had the highest academic dishonesty rate (2) there was no difference in academic dishonesty based on the type gender (3) there were differences in the level of interaction of academic dishonesty in terms of majors and gender, namely students in the electric power installation engineering department had the lowest level of academic dishonesty than the other groups. It can be concluded that there are differences in the level of academic dishonesty in terms of affairs, there are no differences in academic dishonesty based on gender and there are differrences in the interaction between the level of academic dishonesty in terms of majors and gender.